Analyzing Cost Efficiency Elements in Virtual Teams Application : A Systematic Review - Merrylien Rayo, Natashia; Fabiola Rayo, Edwina; Ronald Sumanti, Elvis (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to understand the critical elements influencing the cost-effectiveness of virtual teams and their strategic application in enterprises. Research methodology: The research uses a literature review to assess the organizational dynamics, money allocation, and efficiency of virtual teams. Results: The study finds that investing in technology, especially communication platforms, is crucial. Savings are identified in team development, office space, travel costs, and communication expenses. Limitations: The research relies heavily on prior studies, limiting its generalizability and requiring adaptation to rapid technological changes.